Large-eddy simulation of methane direct injection using the full injector geometry. (15th April 2021) - Yosri, M.R.; Ho, J.Z.; Meulemans, M.; Talei, M.; Gordon, R.L.; Brear, M.J.; Cosby, D.; Lacey, J.S.
Highlights: LESs of methane DI into CVC from an outward opening injector were performed. A new post-processing method was introduced to compare the LES results with schlieren images. LES results were validated using experimental data and theories from the literature. LES of the full injector provides the required information for simulating a simpler injector. The nozzle pressure ratio has a significant impact on the external flow characteristics. Abstract: Understanding the mixing process of under-expanded gaseous-fuel jets from an outward opening injector is essential for developing Direct Injection (DI) internal combustion engines. This paper presents a Large-Eddy Simulation (LES) study of the DI of methane into a Constant Volume Chamber (CVC), considering the full, internal geometry of a prototype injector. Four cases at conditions relevant to Compressed Natural Gas (CNG) DI engines are investigated, with methane as a surrogate for CNG. A new post-processing method permits the 3D LES field to be projected into a 2D density gradient field that can be compared to a schlieren image. The LES results are then validated against high-speed, schlieren imaging experiments, demonstrating that the simulations are able to reproduce experimental trends. Three main regions of the external flow are observed: a recirculation zone just downstream of the injector tip, a stagnation zone and a far-mixing zone. The location of the stagnation zone increases as the CVC pressure decreases, consistent with a theory presented in the literature. The modelling of the full internal geometry of the injector leads to a determination of the injector pressure losses. Once the pressure loss within the injector is considered, a short version of the injector can reasonably represent the full injector for prediction of the external flow.